2002
DOI: 10.1007/bf02482087
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of test specimens on tensile splitting strength of concrete: general relation

Abstract: A broad experimental program was carried out on cubes, cylinders and prisms (loaded transversally or longitudinally) of sizes usually used in laboratory testing. For casting, concrete mixes of various compositions were used. The 1600 results obtained were evaluated by mathematical statistical methods. The volume of test specimens was substituted either by the size of the corresponding fracture area or by the size of the highly stressed volume (HSV) in their loaded cross-section; The absolute values of the tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 4 publications
0
26
0
2
Order By: Relevance
“…There are three types of tests to measure strength in tension: direct tension, flexure, and splitting tension. 6 It has been well established that the simplest and the most reliable method, which generally provides a lower coefficient of variation, is the splitting tensile test [7][8][9] of a cylindrical specimen. In this test, a cylindrical specimen is loaded in compression diametrically between two plates.…”
Section: Introductionmentioning
confidence: 99%
“…There are three types of tests to measure strength in tension: direct tension, flexure, and splitting tension. 6 It has been well established that the simplest and the most reliable method, which generally provides a lower coefficient of variation, is the splitting tensile test [7][8][9] of a cylindrical specimen. In this test, a cylindrical specimen is loaded in compression diametrically between two plates.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in Materials Science and Engineering 5 [28], and Rocco et al [29,30] show that the tensile splitting strength of concrete is strongly determined by the size of test specimen. Wide range of experimental studies were carried out on cubes, cylinder, and prisms to investigate the size effect of tensile splitting strength by Kadleček et al [31]. It was demonstrated that the size effect highly depends on the areas of splitting fracture section rather than the shape of test specimens, which creates a unifying measurement for size effect.…”
Section: Strength Calculationmentioning
confidence: 99%
“…A generalized size effect formula was presented, which can be applied to cores or cubes obtained from existing structures. According to Kadleček et al [31], the tensile splitting strength of concrete cores was converted to the strength of standard test specimen (150 × 150 × 150 mm). The size effect formula is given as [31] = ts,cor…”
Section: Strength Calculationmentioning
confidence: 99%
“…Similarly, Kadlecek et al . proposed some empirical formulas including size‐dependent responses for predicting the split‐tensile strength of the cube, cylinder and prism specimens. A recent approach also based on the redistribution of stress, by Karihaloo , predicts trends that are identical to those of Bazant's approach at the large‐scale end but differ from them when the structural size is small.…”
Section: Size Effect In Concrete Fracturesmentioning
confidence: 99%